2020
DOI: 10.1101/2020.06.17.157826
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conclusive Identification of Senescent T Cells Reveals Their Abundance in Aging Humans

Abstract: Aging leads to a progressive functional decline of the immune system, which renders the elderly increasingly susceptible to disease and infection. The degree to which immune cell senescence contributes to this functional decline, however, remains unclear since methods to accurately identify and isolate senescent immune cells are missing. By measuring senescence-associated ß-galactosidase activity, a hallmark of senescent cells, we demonstrate here that healthy humans develop senescent T lymphocytes in peripher… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In agreement with prior evidence linking short leukocyte telomeres to poor COVID-19 outcomes [1], our data implicate CD4 + T cell aging as a predominant driver for immunopathology in patients with advanced ages where additional agerelated immune remodeling may have been plateaued. CD8 + T cell senescence outpaces CD4 + counterparts over time [22,23]. While SARS-CoV-2-reactive CD8 + T cell memory compartments show particular vulnerabilities to aging [20], our findings highlight CD4 + T cell integrity as central to antiviral responses in this elderly cohort.…”
Section: Discussionmentioning
confidence: 64%
“…In agreement with prior evidence linking short leukocyte telomeres to poor COVID-19 outcomes [1], our data implicate CD4 + T cell aging as a predominant driver for immunopathology in patients with advanced ages where additional agerelated immune remodeling may have been plateaued. CD8 + T cell senescence outpaces CD4 + counterparts over time [22,23]. While SARS-CoV-2-reactive CD8 + T cell memory compartments show particular vulnerabilities to aging [20], our findings highlight CD4 + T cell integrity as central to antiviral responses in this elderly cohort.…”
Section: Discussionmentioning
confidence: 64%
“…For instance, it was reported that similar to other somatic cells, peripheral blood mononuclear cells (PBMCs) in humans strongly display classical markers of cellular senescence such as high SA-β-gal activity, p16 Ink4a overexpression, telomere dysfunction, and impaired proliferative response (Martínez-Zamudio et al 2021). Interestingly, the authors noted that the senescent CD8 + T cells population (including TEM and TEMRA subsets) developed unique SASP-associated gene expression profile as compared to senescent fibroblasts, and such T cells reached average levels of 64% in aging subjects thereby suggesting that T cell senescence substantially overlaps with replicative senescence in non-leucocyte cells and that such senescent T cells could be far more abundant in circulation than previously thought (Martínez-Zamudio et al 2021). Another recent work demonstrated that the development of p16 Inka4a mediated cellular senescence and suppressed proliferative response is a characteristic of aging human T cells which could be a potential therapeutic target (Janelle et al 2021).…”
Section: Cellular Senescence In Immune Cells: Characteristics and Impactmentioning
confidence: 99%
“…The age and status of T cells are tracked by their cell-surface markers, as they do not express the costimulatory molecules CD27 and CD28, but do express CD57 and KLRG1, both of which function to reduce the proliferative capacity [ 46 ]. Senescent CD8 + T cells have recently been shown to increase in abundance in older donors with a twofold increase compared with younger donors in their early 20s, suggesting their major contribution to a reduced immune function and enhanced susceptibility to disease [ 47 ].…”
Section: Diabetes Mellitus-associated T Cell Senescencementioning
confidence: 99%